Optimalisasi Peningkatan Derajat Kesehatan Remaja Melalui Pemberdayaan Masyarakat Kelompok Remaja Dengan Peer Educator di Kelurahan Ladang Bambu Kecamatan Medan Tuntungan - Rizky Andriani Bakara; Helena Fransysca (Indonesian Journal Publisher, 2021)
Adolescent individuals are often involved in conflicts and have many problems, both problems with themselves or with the environment outside themselves. Many teenagers are not ready to compensate for the changes they experience, such as physical changes, emotional levels, morals, social interactions and ways of acting and thinking. Recently, during the spread of the coronavirus, many teenagers only spend time sleeping and then wake up to study online or play gadgets. This raises concerns about changes in adolescents' conditions, especially their psychological conditions. Teenagers are preoccupied with online schooling which makes them busier in the virtual world than in the real world. This, not only causes boredom for adolescents, but also has an effect on adolescent mental health, so they need a partner who can help with the problems experienced. This community service intends to improve the degree of adolescent health by empowering adolescents through Peer Education of their own friends within the scope of the organization in the context of monitoring growth and development with tools in the form of Adolescent Health Cards (KMS) and simulations as a vehicle for empowering adolescents in improving peer counselor skills. The approach method offered to solve the problems of program partners that have been agreed upon using a survey approach, namely data collection in Ladang Bambu Village, Medan Tuntungan Subdistrict with observational data collection methods by means of field observation. Implementation is carried out according to a predetermined schedule by gathering teenagers who have become members together. The results of community service have increased knowledge, attitudes, behavior of adolescents about the function of reproductive organs and trained in organization so that peer education can be formed.